Essential oil profile of major populations Zingiber officinale Rosc. utilized in Malaysia for traditional medicine - Charles Santhanaraju Vairappan; Ong, Jit Beng; Thilahgavani Nagappan; Januarius Gobilik; Tulasiramanan Ramachandram (Penerbit Universiti Malaysia Sabah, 2012)
Zingiberaceae is one of the largest ginger families of the plant kingdom and are often regarded as an important herbaceous species.